What Secondary Teachers Need in Professional Development - Lucilio, Lisa (Catholic Education: A Journal of Inquiry and Practice, 2009)
Most dioceses do not have well-articulated, systematic approaches to the professional development of Catholic school teachers and administrators. This article summarizes current research on effective strategies for professional development and reports on a study of one Midwestern diocese regarding the needs, perceptions, and plans of teachers and principals at the high school level.